Research Information Systems – fit for the future? A report on the situation and plans of the University of Sheffield Library - Clarke, Tracey; Bussey, Andy (o-bib. Das offene Bibliotheksjournal / Herausgeber VDB, 2018)
This article discusses the University of Sheffield’s rationale for joining, and the experience of participating in, the Development Partner Programme for Ex Libris’ Esploro product.  It should be noted that the article expresses the opinions of the University of Sheffield Library staff writing the article, and not the Ex Libris company.